Clinical trials of new drugs for the treatment of rheumatoid arthritis: focus on early disease. Issue 7 (1st April 2016) - Smolen, Josef S; Collaud Basset, Sabine; Boers, Maarten; Breedveld, Ferdinand; Edwards, Christopher J; Kvien, Tore K; Miossec, Pierre; Sokka-Isler, Tuulikki; van Vollenhoven, Ronald F; Abadie, Eric C; Bruyère, Olivier; Cooper, Cyrus; et al.
Abstract : The European Society for Clinical and Economic Aspects of Osteoporosis, Osteoarthritis and Musculoskeletal Diseases convened a task force of experts in rheumatoid arthritis (RA) and clinical trial methodology to comment on the new draft 'Guideline on clinical investigation of medicinal products for the treatment of RA' released by the European Medicines Agency (EMA). Special emphasis was placed by the group on the development of new drugs for the treatment of early RA. In the absence of a clear definition of early RA, it was suggested that clinical investigations in this condition were conducted in disease-modifying antirheumatic drugs naïve patients with no more than 1 year disease duration. The expert group recommended using an appropriate improvement in disease activity (American College of Rheumatology (ACR) or Simplified/Clinical Disease Activity Index (SDAI/CDAI) response criteria) or low disease activity (by any score) as primary endpoints, with ACR/European League Against Rheumatism remission as a secondary endpoint. Finally, as compelling evidence showed that the Disease Acrivity Score using 28-joint counts (DAS28) might not provide a reliable definition of remission, or sometimes even low disease activity, the group suggested replacing DAS28 as a measurement instrument to evaluate disease activity in RA clinical trials. Proposed alternatives included SDAI, CDAI and Boolean criteria.